Seni Tilawah Al-Qur’an Dalam Pembentukan Karakter - Mastur; Mu'aidi; Sabaruddin; Badaruddin (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2022)
Read the Qur’an in tartil, but it is an inseparable part of human existence as a cultured creature who has creativity, taste, and intention. Art is a part of culture. Culture is the result of cultivation creation for humans themselves, and society grows because of culture. Muhsin Salim further explained that art as the embodiment of a sense of beauty, in general, is for the welfare of life. Art arises through the recitation of the Koran which is the result of the process of learning the songs of the Koran. Understanding character is innate, heart, soul, personality, character, behavior, personality, nature, character, temperament, character. The character is personality, behavior, character, character, and character. Character refers to a series of attitudes, behaviors, motivations, and skills. Learning is an effort to teach students. Meanwhile, according to Suyudi, learning is a process to acquire knowledge, while knowledge is a way to obtain truth or value, and truth is a statement without hesitation that begins with an attitude of doubt first. The art of reading the Qur'an known as An-Naghom fil Qur'an means to beautify the sound of the recitation of the Qur'an. Learn ways or methods of humming, singing, and beautifying the sound of the recitation of the Qur'an. The art of reading the Qur'an is an oral science. Based on the description above, it can be concluded as follows: In general, the implementation of character education at the Nurul Quran Praya Islamic Boarding School, Central Lombok has been carried out in an integrated manner in the learning process, both held in formal education such as Islamic Junior High Schools and Madrasah Aliyah institutions as well as extracurricular programs developed in hostels, such as the Al-Quran Recitation art education program, implementation of integrated character education at the vision-mission level, and the goals of the Nurul Qur’an Praya Islamic Boarding School, Central Lombok. Character formation through the art of recitation of the Qor’an includes characters related to perseverance, patience, responsibility, cooperation, and religion. These characters grow from the processes of habituation that take place continuously through education in the art of recitation of the Koran. The most prominent characters include the character of perseverance, patience, responsibility, cooperation, and religion. Indicators of the formation of the character of students through the art of recitation of the Koran can be seen from values such as the patience of students, the character of responsibility, obedience, and obedience, a climate of cooperation, and the religious situation that characterizes the lives of students. The religious atmosphere is reflected in the culture of greetings, clothing and clothing, obedience and obedience of students, manners, worship, reciting, and morals that are reflected in the lives of students in the Al-Quran Recitation art program at the Nurul Qur’an Praya Islamic Boarding School, Central Lombok. Keywords: Character Formation, Santri, Art of Recitation.